Lınguocultural Analysıs Of The Concept “Joy” / “Pitcher” In Englısh And Uzbek - SaydamatovIkromjon Nazirovich, ZulkhanovMustafoJuraevich, Abdulkarimova Kamila Akramovna, FayziyevaNilufarNemat qizi (International Journal of Advanced Science and Technology, 2020)
This article is devoted to linguoculturological analysis of the concept "joy"/"кувонч" in English and Uzbek. Due to the increased interest of scientists in anthropological problems, the concept of “joy” occupies one of the central positions in understanding the human nature, as well as in determining the development of culture and civilization. Most linguists claim that “joy” is a key component of the worldview and is one of the ancient and universal concepts.Linguoculturological analysis of this concept contributes to the study of the spiritual, cultural and social essence of the ethnos. A comparative analysis of the implementation of the concept of “joy” based on the material of two diverse systems of languages - English and Uzbek - contributes to a more complete disclosure of the specifics of the national mentality of the aforementioned peoples.